Analisis studi kelayakan pembangunan sport center di area lapangan Tambakboyo Kecamatan Ambarawa Kabupaten Semarang - Komala Inggarwati; Amanda Salsabila Hadi; Marino Firaj Kausar; Mei Prihatiningsih (Universitas Widya Mataram, 2022)
A healthy lifestyle is human necessity to maintain health and fitness. Therefore, the community requires sports facilities. The field area in Tambakboyo is a suitable location for sports center facilities considering that there are no sports facilities for the local community. This sports center considers several aspects, they are technical aspects, management aspects, financial aspects and environmental aspects. By combining quantitative and qualitative data, also descriptive research methods, it was found that the analysis of the market aspect of the sports area development project shows that Tambakboyo field has the potential to become a sports center. The analysis of the technical aspect shows that the location is quite strategic. The management, financial and environmental aspects show that the plan of building a sports area proved feasible to be realized with the expectation of improving the welfare and health level of the local community.